Loudness summation of equal loud narrowband signals in normal-hearing and hearing-impaired listeners. (25th May 2018) - Ewert, Stephan D.; Oetting, Dirk
Abstract: Objective : Loudness perception of binaural broadband signals, e.g. speech shaped noise, shows large individual differences using frequency-dependent amplification which was adjusted to restore the loudness perception of monaural narrowband signals in hearing-impaired (HI) listeners. To better understand and quantify this highly individual effect, loudness perception of broadband stimuli consisting of a number of spectrally separated narrowband components which where individually adjusted to equal loudness is of interest. Design : Based on categorical loudness scaling, the loudness of an equal categorical loudness noise (ECLN) consisting of six third-octave noises was assessed. For loudness categories "medium" und "very loud" the required narrowband loudness was analysed. Study sample : Nine normal-hearing (NH) and ten HI listeners. Results : HI listeners showed lower narrowband loudness values compared to NH listeners, indicating an increased spectral loudness summation. More than 50% of the HI listeners showed higher binaural spectral loudness summation compared to NH listeners. The amount of binaural spectral loudness summation was highly correlated ( r 2 = 0.92) with the loudness level at "very loud" of aided speech shaped noise. Conclusions : The suggested ECLN measurement is suited to assess individual (binaural) broadband loudness in aided conditions, providing valuable information for hearing-aid fitting.